(untitled) (Bangladesh Journal of Plant Taxonomy, 2021)
Earlier, we have established that the European blackjack, which in many literary sources is cited as an invasive North American Bidens connata, was described by Carl Warnstorf back in 1895 as B. decipiens and had a hybrid origin (B. frondosa × B. cernua). In this study, we continue to compare the genomes of B. connata and B. decipiens by molecular genetics and cytological methods. The objects are the F1 offsprings of B. frondosa, B. connata, and B. cernua collected in 2018 from Minnesota and Wisconsin (USA), grown from seeds in the greenhouse conditions of N.V. Tsitsin Main Botanical Garden of Russian Academy of Sciences, as well as samples of B. decipiens, B. frondosa and B. cernua collected from Eastern Europe (Belarus and European Russia). The nucleotide sequences of nuclear (ITS 1–2) and chloroplast (trnL– trnF and rpl32–trnL) DNA were studied. Analysis of the ITS 1–2 site showed that B. connata individuals of North America are not hybrids. Analysis of the chloroplast DNA regions confirmed that both taxa, B. connata and B. decipiens, are evolutionarily close to B. cernua. Bangladesh J. Plant Taxon. 28(1): 1-10, 2021 (June)